Frequency anomalies and characteristics of extratropical cyclones during extremely wet, dry, windy and calm seasons in the extratropics - Binder, Hanin; Wernli, Heini (2024)
Extreme meteorological seasons are highly relevant because of their severe impacts on many socioeconomic sectors. However, a global statistical characterisation of observed extreme seasons is challenging, because at any specific location only very few such seasons occurred during the limited period with available reanalysis data sets. This study therefore uses 1050 years of present-day (1990–1999) climate simulations of the Community Earth System Model Large Ensemble (CESM-LE) to systematically identify extremely wet, dry, windy and calm seasons in the Northern Hemisphere (NH) and Southern Hemisphere (SH) extratropics during winter and summer, and to quantify the role of extratropical cyclones for their occurrence. Extreme seasons are defined as spatially coherent regions of extreme seasonal mean precipitation or near-surface wind. Compared to the climatology, extremely wet seasons are associated with positive anomalies in cyclone frequency in large parts of the extratropics. In the SH storm track and at the downstream ends of the NH storm tracks, cyclones contributing to wet winters are also anomalously intense and typically originate unusually far to the west and south, while in the subtropical North Atlantic and over the eastern Mediterranean they are on average more stationary than climatologically. During wet summers, many continental regions are not associated with strong anomalies in any of the cyclone characteristics (e.g., most of North America, the coastal regions around the Mediterranean Sea and southern Asia), which points to the importance of other processes like convection, orographic ascent or, over southern Asia, monsoon precipitation. Windy seasons are often associated with anomalously few, but particularly intense cyclones, especially during winter. Positive anomalies in both cyclone frequency and intensity are found in the southern North Atlantic during winter, which suggests that windy winters in this region occur during southward shifts in the position of the main storm track. The ...